2013
DOI: 10.1016/j.bbi.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phenotype markers and neuronotoxic potential of polarised primary microglia in vitro

Abstract: Highlight► A unique catalogue of phenotype markers and neuronotoxic effects of polarised primary microglia, as a comparative tool to screen neurotherapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
549
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 546 publications
(594 citation statements)
references
References 88 publications
28
549
1
2
Order By: Relevance
“…The M1 phenotype has been related to release of pro-inflammatory cytokines, cytotoxicity, radical oxygen species (ROS) release, auto antigen presentation to T cells and therefore contributing with disease progression as has been observed Alzehimer's disease, MS and stroke studies (Chhor et al 2013, Rawji et al 2016). The M2 anti-inflammatory phenotype has been related with the production of anti-inflammatory cytokines and is associated with regeneration properties and wound healing Zhang 2015, Ransohoff andPerry 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The M1 phenotype has been related to release of pro-inflammatory cytokines, cytotoxicity, radical oxygen species (ROS) release, auto antigen presentation to T cells and therefore contributing with disease progression as has been observed Alzehimer's disease, MS and stroke studies (Chhor et al 2013, Rawji et al 2016). The M2 anti-inflammatory phenotype has been related with the production of anti-inflammatory cytokines and is associated with regeneration properties and wound healing Zhang 2015, Ransohoff andPerry 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Microglia/macrophage phenotypes can be recognized by changes in the expression of specific molecules. NOS-2, TNFα, COX-2, and IL-1β are characteristic molecules of a M1 phenotype while arginase-1, CD206, Ym-1 and FIZZ-1 are considered M2-phenotype markers 21 (Chhor et al 2013, Fernando et al 2014, Gensel and Zhang 2015. However, recent studies in vitro and in vivo have revealed that reactive microglia/macrophages are able to co-express M1 and M2 markers.…”
Section: Microglia/macrophage Activation Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…There have been a number of studies that demonstrate the beneficial neuroprotective and neuroreparative effects of M2 switching [68][69][70][71]. These studies have focused on the importance of various M2 markers such as IL-4 [72,73], IL-10 [72,74,75], IL-1RA [76], TGF-β [77,78], CD206 [72,79], arginase 1 [79,80], granulocyte macrophage colony-stimulating factor [72], insulin-like growth factor 1 [81,82], and peroxisome proliferator-activated receptor-γ [70,71,83]. Even though our understanding of the role of these individual factors have become more insightful, it is very difficult to achieve beneficial neuroprotective effects by modulating just one of these factors.…”
Section: Targeting Microglia As a Therapeutic Strategymentioning
confidence: 99%
“…As a result, they may contribute to injury progression. M2 populations on the other hand are believed to play a role in angiogenesis, remodeling of the extracellular matrix, and support regeneration following injury [103]. When appropriately queued, microglia can also release neurotrophins to augment neuronal growth and survival [104].…”
Section: Mechanisms Of Neural Injury In the Traumatic Penumbramentioning
confidence: 99%